Extremely low temperature resistant gel electrolyte and preparation method and application thereof

By introducing maltitol into the gel electrolyte, the dendrite and corrosion problems of gel electrolyte under extremely low temperature conditions are solved, high and low temperature conductivity and excellent mechanical properties are achieved, and the extremely low temperature performance and safety of zinc-air batteries are improved.

CN119542523APending Publication Date: 2025-02-28HEILONGJIANG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411776966.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing gel electrolytes have problems such as dendrite, corrosion, passivation, etc. under extremely low temperature conditions, and it is difficult to take into account both mechanical properties and ionic conductivity, which increases the volatility and flammability of zinc-air batteries and limits their application in extreme environments.

Method used

By introducing the hydrophilic substance maltitol into the gel electrolyte, the dendrite and corrosion phenomenon at the interface between the electrolyte and the zinc anode is changed, while inhibiting the freezing of solvent water, improving the extremely low-temperature performance of the gel.

Benefits of technology

The excellent cycle stability and high and low temperature conductivity of gel electrolyte under -60°C are achieved, which improves the mechanical properties and extremely low temperature properties of zinc-air batteries, and reduces volatility and flammability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542523A_ABST
    Figure CN119542523A_ABST
Patent Text Reader

Abstract

The invention discloses an extremely low temperature resistant gel electrolyte and a preparation method and application thereof, and belongs to the technical field of gel electrolytes and preparation thereof. The problems that an existing gel electrolyte is prone to freezing at low temperature, and the mechanical property and the ionic conductivity are difficult to consider at the same time are solved. According to the invention, the hydrophilic substance maltitol is introduced into the gel electrolyte, so that the phenomena of dendritic crystal, corrosion, passivation and the like at the interface of the electrolyte and a zinc anode are relieved without introducing an organic solvent, and meanwhile, the introduced maltitol destroys the hydrogen-bond interaction between deionized water, so that the freezing of solvent water is inhibited; according to the present invention, the ultra-low temperature performance of the gel is improved, the ultra-low temperature resistance of the gel electrolyte is ensured, the gel electrolyte has excellent cycle stability under the condition of-60 DEG C 10 mAcm <-2 >, and the obtained gel electrolyte further has excellent mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an extremely low temperature resistant gel electrolyte and a preparation method and application thereof, belonging to the technical field of gel electrolyte and preparation thereof. Background Art

[0002] Low temperature energy storage devices are essential equipment in extremely cold climates such as space exploration, polar exploration and high-altitude activities. Rechargeable zinc-air batteries have a high theoretical energy density (up to 1086Wh kg -1 ), the negative electrode material is metallic zinc (Zn), which is abundant in the earth's crust. The positive electrode active material is oxygen (O2), which greatly reduces the weight of the battery and has the advantage of low cost. As an important component of the energy storage device, the antifreeze of the electrolyte directly affects the low-temperature performance of the energy storage device.

[0003] The electrolyte of zinc-air battery can be divided into aqueous electrolyte and gel polymer electrolyte, both of which have extremely high safety. Among them, the quasi-solid-state zinc-air battery with gel polymer as electrolyte can work stably at extremely low temperature (-60℃). This is because compared with liquid electrolyte, gel polymer electrolyte has rich polar groups and three-dimensional network structure, which effectively alleviates the corrosion problem of negative electrode, promotes the dissolution of zinc ions, inhibits Zn dendrites, and thus constructs a stable Zn / / electrolyte interface. However, the existing technology mainly introduces organic solvents into gel polymer electrolytes to inhibit the activity of water molecules, reduce side reactions and the growth of zinc dendrites, but these methods have limited effect on alleviating the passivation effect, and there is a problem that it is difficult to balance mechanical properties and ionic conductivity. At the same time, it increases the volatility and flammability of gel polymer electrolytes, which greatly limits the development of flexible zinc-air batteries and their practical applications in extreme environments, and needs to be improved and developed. Summary of the invention

[0004] In view of the above problems existing in the existing gel electrolyte, the present invention provides an extremely low temperature resistant gel electrolyte and a preparation method and application thereof.

[0005] The technical solution of the present invention:

[0006] One of the purposes of the present invention is to provide a method for preparing a very low temperature resistant gel electrolyte, the method comprising the following steps:

[0007] (1) adding acrylamide to deionized water and stirring for the first time, then adding maltitol and stirring for the second time, then adding a crosslinking agent and an initiator and stirring for the third time, and heating and polymerizing after the stirring is completed to obtain a gel precursor;

[0008] (2) Immersing the gel precursor in an electrolyte to obtain an extremely low temperature resistant gel electrolyte.

[0009] It is further defined that the molar ratio of acrylamide, deionized water, maltitol, crosslinking agent and initiator in (1) is 100:1-5:300-700:001-0.04:0.05-0.2.

[0010] It is further defined that the molar ratio of acrylamide, deionized water, maltitol, crosslinking agent and initiator is 100:3:600:0.03:0.01.

[0011] It is further defined that the crosslinking agent in (1) is N,N-methylenebisacrylamide, dicumyl peroxide, bis-2,4-dichlorobenzoyl peroxide, poly(1,4-butylene diacrylate) or ethylene glycol dimethacrylate;

[0012] It is further defined that the initiator in (1) is azobisisobutyronitrile, azobisisoheptylnitrile, ammonium persulfate, 2-hydroxy-4,-(2-hydroxyethoxy)-2-methylpropiophenone or diisopropyl peroxydicarbonate.

[0013] It is further defined that the first stirring temperature in (1) is 0 to 40° C. and the time is 20 to 40 min.

[0014] It is further defined that the second stirring temperature in (1) is 0-40°C and the time is 30-60 min.

[0015] It is further defined that the third stirring temperature in (1) is 50-100° C. and the time is 5-20 h.

[0016] It is further defined that the heating polymerization temperature in (1) is 50 to 100° C. and the time is 5 to 15 hours.

[0017] It is further defined that the electrolyte in (2) is a mixed solution of alkali solution and zinc salt.

[0018] The second object of the present invention is to provide an extremely low temperature resistant gel electrolyte prepared by the above method, wherein the gel electrolyte has excellent cycle stability when used under -60°C conditions.

[0019] The third object of the present invention is to provide an application of the extremely low temperature resistant gel electrolyte, specifically for preparing zinc-air batteries.

[0020] Beneficial effects:

[0021] The present invention introduces the hydrophilic substance maltitol into the gel electrolyte, thereby alleviating the phenomena of dendrite, corrosion, passivation and the like at the interface between the electrolyte and the zinc anode without introducing an organic solvent. The introduced maltitol also destroys the hydrogen bonding between deionized water, thereby inhibiting the freezing of the solvent water, improving the extremely low temperature performance of the gel, ensuring the extremely low temperature resistance of the gel electrolyte, and the obtained gel electrolyte also has excellent mechanical properties.

[0022] The gel electrolyte prepared by the invention has rich pore structure, good low temperature tolerance and high low temperature conductivity. The zinc-air battery assembled with the gel electrolyte can be 10mAcm at -60℃. -2 It has excellent cycle stability under certain conditions.

[0023] In addition, the preparation process of the gel electrolyte provided by the present invention is simple and low in cost. The entire preparation process is simple and highly operable, which is convenient for use in low-temperature energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 1H (D2O) nuclear magnetic resonance spectra of the gel electrolytes prepared in Examples 1 to 3 and Comparative Example 1;

[0025] Figure 2 FTIR spectra of the gel electrolytes prepared in Examples 1 to 3 and Comparative Example 1;

[0026] Figure 3 The molecular dynamics (MD) simulation results (the number of hydrogen bonds) of the gel electrolytes prepared in Example 1 and Comparative Example 1;

[0027] Figure 4 This is a SEM photo of the gel electrolyte prepared in Example 1;

[0028] Figure 5 The stress-strain curves of the gel electrolytes prepared in Examples 1 to 3 and Comparative Example 1 at room temperature are shown;

[0029] Figure 6 AFM photos of the anode of the zinc-air battery assembled in Example 1 and Comparative Example 1 after cyclic charge and discharge;

[0030] Figure 7 The zinc-air battery assembled for Example 1 and Comparative Example 1 was heated at -60°C and 1 mA·cm -2 Lower cycle test chart;

[0031] Figure 8 The zinc-air batteries assembled from Examples 1 to 3 and Comparative Example 1 were heated at room temperature and 50 mA·cm -2 Lower cycle test chart;

[0032] Fig. 9 This is a comparison diagram of the ionic conductivity of the gel electrolytes prepared in Example 1 and Comparative Example 1 at different temperatures;

[0033] Fig.10 The voltage, current density and power density of the zinc-air battery assembled for Example 1 and Comparative Example 1;

[0034] Fig.11The zinc-air battery assembled in Example 1 was heated at -60°C and 10 mA·cm -2 Lower cycle test chart;

[0035] Fig.12 The zinc-air battery assembled for Example 1 and Comparative Examples 2-3 was tested at -40°C and 5 mA·cm -2 Lower cycle test chart;

[0036] Fig.13 The following are actual photos of the zinc-air batteries assembled in Example 1 and Comparative Examples 2-3 at a temperature of -60°C. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0040] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.

[0041] Example 1

[0042] The process of preparing the extremely low temperature resistant gel electrolyte (0.3 m Maltitol) in this embodiment is as follows:

[0043] (1) Dissolve 10 mol of acrylamide in 60 mol of deionized water and stir at 25°C for 30 min to fully dissolve the acrylamide;

[0044] (2) adding 0.3 mol of maltitol to the acrylamide solution and stirring at 25° C. for 40 min;

[0045] (3) Add 3 mmol N,N-methylenebisacrylamide and 1 mmol ammonium persulfate to (2) and stir thoroughly at 25°C for 10 h;

[0046] (4) pouring the solution obtained in (3) into a polytetrafluoroethylene membrane, placing it in an oven at 61° C. for cross-linking polymerization for 10 h to obtain a gel precursor;

[0047] (5) The gel precursor was immersed in a mixed aqueous solution of 6 mol / L KOH and 0.2 mol / L Zn(AC)2 for 7 days to obtain a gel electrolyte, which was recorded as a 0.3 m Maltitol sample.

[0048] The microstructure of the obtained 0.3m Maltitol was characterized, and the results are as follows: Figure 4 As shown by Figure 4 It can be seen that the 0.3mMaltitol sample has a porous structure, and the rich pore structure is conducive to the conduction of ions and prolongs the cycle life of the battery at low temperatures.

[0049] (6) Preparation of zinc electrode: Cut the zinc foil into a rectangular structure of 3*4 cm, and then polish the surface smooth with sandpaper.

[0050] (7) Preparation of air electrode: Select an air electrode carrying a non-precious metal bifunctional catalyst (Co3O4) and cut it into a rectangle of the same size as the zinc foil.

[0051] (8) Cut the 0.3 m Maltitol sample prepared in step 5) into a rectangle of the same size as the zinc electrode and air battery.

[0052] (9) The zinc electrode, gel electrolyte, and air electrode are assembled into a sandwich structure in a bottom-up order and then packaged to form a flexible zinc-air battery.

[0053] Example 2

[0054] The difference between this embodiment and embodiment 1 is that the amount of maltitol used in (2) is 0.2 mol, and the remaining process steps and parameter settings are the same as those in embodiment 1. The obtained gel electrolyte is recorded as 0.2 m Maltitol sample.

[0055] Example 3

[0056] The difference between this embodiment and embodiment 1 is that the amount of maltitol used in (2) is 0.4 mol, and the remaining process steps and parameter settings are the same as those in embodiment 1. The obtained gel electrolyte is recorded as 0.4 m Maltitol sample.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 1 is that the amount of maltitol used in (2) is 0 mol, and the remaining process steps and parameter settings are the same as those in Example 1. The obtained gel electrolyte is recorded as the Without Maltitol sample.

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 1 is that 0.3 mol pectin is used in (2) to replace 0.3 mol maltitol, and the remaining process steps and parameter settings are the same as those in Example 1. The obtained gel electrolyte is recorded as Comparative Example 2 sample.

[0061] Comparative Example 3

[0062] The difference between this comparative example and Example 1 is that 0.3 mol of carboxymethyl cellulose is used instead of 0.3 mol of maltitol in (2), and the remaining process steps and parameter settings are the same as those in Example 1. The obtained gel electrolyte is recorded as Comparative Example 3 sample.

[0063] Effect example

[0064] (1) The gel electrolytes prepared in Examples 1 to 3 and Comparative Example 1 were subjected to NMR and IR tests. The results were as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that with the increase of maltitol content, the electrolyte undergoes a significant chemical shift change to the low field. This indicates that maltitol interacts with free D2O molecules in the D2O environment and destroys the hydrogen bond network between D2O molecules. Figure 2 It can be seen that with the increase of maltitol concentration, the observed red shift indicates that the hydrogen bonding interaction between water molecules in the system is enhanced. This is because the polyhydroxy structure on maltitol can also form hydrogen bonds with H2O and change the hydrogen bonding network structure of H2O.

[0065] (2) MD simulation calculation was performed on the gel electrolytes prepared in Example 1 and Comparative Example 1. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the addition of 0.3m maltitol reduces the number of water-water hydrogen bonds in the comparative example from 700 to 300, and forms a new type of hydrogen bond between maltitol and water. This further proves that the addition of maltitol changes the hydrogen bond network structure of H2O, thereby inhibiting the freezing of solvent water, improving the extremely low temperature performance of the gel, and ensuring the extremely low temperature resistance of the gel electrolyte.

[0066] (3) The mechanical properties of the gel electrolytes prepared in Examples 1 to 3 and Comparative Example 1 were tested. The stress-strain curves at room temperature are shown in FIG. Figure 5 As shown. Figure 5It can be seen that the gel electrolyte with added maltitol has excellent mechanical properties and the tensile strength can reach 120KPa. This is mainly because polyacrylamide serves as the first polymer network, and the addition of maltitol forms a second polymer network in polyacrylamide, which makes the gel electrolyte have a double network, which can effectively disperse the stress applied by the outside world and thus has excellent mechanical properties.

[0067] (4) The zinc-air battery assembled in Example 1 and Comparative Example 1 was heated at -60°C and 10 mA·cm -2 The surface microstructures of the zinc anodes of the two batteries were characterized after 20 cycles of charge and discharge. The AFM photos are shown in Figure 6 As shown. Figure 6 It can be seen that after the zinc-air battery assembled in Example 1 is cyclically charged and discharged, the difference between the highest point and the lowest point on the zinc anode surface is 219.2nm. After the zinc-air battery assembled in Comparative Example 1 is cyclically charged and discharged, the difference between the highest point and the lowest point on the zinc anode surface is 428nm, which indicates that the reversibility of zinc is better after adding maltitol.

[0068] (5) The cycle charge and discharge performance of the zinc-air battery assembled in Example 1 and Comparative Example 1 was tested at -60°C and 1 mA·cm -2 Comparison of charge and discharge time in the next cycle Figure 7 As shown by Figure 7 It can be seen that the zinc-air battery assembled in Example 1 has a longer cycle charge and discharge time and a greater number of cycles, especially in terms of cycle charge and discharge time, which is more than three times that of the zinc-air battery assembled in Comparative Example 1.

[0069] (6) The cycle charge and discharge performance of the zinc-air batteries assembled in Examples 1 to 3 and Comparative Example 1 was tested at room temperature and 50 mA·cm -2 Comparison of charge and discharge time in the next cycle Figure 8 As shown by Figure 8 It can be seen that the cycle stability of the zinc-air battery assembled in Example 1 is the best, followed by the zinc-air battery assembled in Example 2, and then the zinc-air battery assembled in Example 3. The cycle stability of the zinc-air battery assembled in Comparative Example 1 is the worst, which is more than twice worse than that of the zinc-air battery assembled in Example 1.

[0070] (7) The ionic conductivity of the gel electrolytes prepared in Examples 1 to 3 and Comparative Example 1 was tested. The results are as follows: Fig. 9 As shown, there are Fig. 9 It can be seen that the ionic conductivity of the gel electrolyte prepared in Example 1 is higher than that of the gel electrolyte without maltitol in Comparative Example 1, and the difference between the two is the largest at -60°C. This shows that the introduction of maltitol is beneficial to improving the ionic conductivity of the gel electrolyte, and the performance is more obvious at low temperatures.

[0071] (8) The voltage, current density and power density of the zinc-air batteries assembled in Example 1 and Comparative Example 1 were tested. The results are as follows: Fig.10 As shown by Fig.10 It can be seen that the power density of the zinc-air battery assembled in Example 1 is as high as 53.5 mW / cm 2 , while the power density of the zinc-air battery assembled in Comparative Example 1 is 41.3 mW / cm 2 , which indicates that the addition of maltitol can increase the discharge rate of zinc-air batteries.

[0072] (9) The zinc-air battery assembled in Example 1 was heated at -60°C and 10 mA cm -2 The cycle charge and discharge test was carried out under the conditions, and the results were as follows Fig.11 As shown by Fig.11 It can be seen that the zinc-air battery assembled in Example 1 has a high conductivity at -60℃ and 10mA cm -2 It can circulate for 85h under the same conditions.

[0073] (10) The zinc-air batteries assembled in Example 1 and Comparative Examples 2 to 3 were heated at -40°C and 5 mA cm -2 The cycle charge and discharge test was carried out under the conditions, and the results were as follows Fig.12 As shown by Fig.12 It can be seen that the cycle stability of the zinc-air battery assembled in Example 1 is the best, followed by the zinc-air battery assembled in Comparative Example 2, and the cycle stability of the zinc-air battery assembled in Comparative Example 3 is the worst, which is more than twice that of the zinc-air battery assembled in the example.

[0074] (11) The zinc-air batteries assembled in Example 1 and Comparative Examples 2-3 were subjected to a low temperature resistance test. The optical photographs of the three batteries at a temperature of -60°C are shown in FIG. Fig.13 As shown by Fig.13 It can be seen that only the zinc-air battery assembled in Example 1 was not frozen.

[0075] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a very low temperature resistant gel electrolyte, characterized in that: include: (1) adding acrylamide to deionized water and stirring for the first time, then adding maltitol and stirring for the second time, then adding a crosslinking agent and an initiator and stirring for the third time, and heating and polymerizing after the stirring is completed to obtain a gel precursor; (2) Immersing the gel precursor in an electrolyte to obtain an extremely low temperature resistant gel electrolyte.

2. The preparation method according to claim 1, characterized in that: (1) The molar ratio of acrylamide, deionized water, maltitol, crosslinking agent and initiator is 100:1-5:300-700:001-0.04:0.05-0.

2.

3. The preparation method according to claim 2, characterized in that: The molar ratio of acrylamide, deionized water, maltitol, crosslinking agent and initiator is 100:3:600:0.03:0.

01.

4. The preparation method according to any one of claims 1 to 3, characterized in that: (1) The crosslinking agent is N,N-methylenebisacrylamide, diisopropylbenzene peroxide, bis-2,4-dichlorobenzoyl peroxide, poly(1,4-butylene glycol diacrylate) or ethylene glycol dimethacrylate.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The initiator in (1) is azobisisobutyronitrile, azobisisoheptanenitrile, ammonium persulfate, 2-hydroxy-4,-(2-hydroxyethoxy)-2-methylpropiophenone or diisopropyl peroxydicarbonate.

6. The preparation method according to claim 1, characterized in that: (1) The first stirring temperature is 0-40°C and the time is 20-40 min; the second stirring temperature is 0-40°C and the time is 30-60 min; the third stirring temperature is 0-40°C and the time is 6-20 h.

7. The preparation method according to claim 1, characterized in that: (1) The heating polymerization temperature is 50°C to 100°C and the time is 5 to 15 hours.

8. The preparation method according to claim 1, characterized in that: (2) The electrolyte is a mixed solution of alkali solution and zinc salt.

9. An extremely low temperature resistant gel electrolyte prepared by the method according to any one of claims 1 to 8, characterized in that: The gel electrolyte is used at -60°C.

10. An application of the extremely low temperature resistant gel electrolyte according to claim 9, characterized in that: Used to prepare zinc-air batteries.

Citation Information

Cited By

  • Zinc ion battery electrolyte based on isomaltitol and maltitol as well as preparation method and application of zinc ion battery electrolyte

    CN121601811A

  • Isomalt and maltitol-based zinc-ion battery electrolyte, preparation method and application thereof

    CN121601811B